2016
DOI: 10.4317/medoral.21026
|View full text |Cite
|
Sign up to set email alerts
|

Positive effect of platelet rich fibrin on osseointegration

Abstract: BackgroundLeukocyte-platelet rich fibrin (L-PRF) is a second generation platelet concentrate clinically used to accelerate tissue healing and bone regeneration. Achieving reduced implant osseointegration time could provide immediate or early loading of implants. The aim of this study was to evaluate the L-PRF-induced osseointegration and bone-implant contact (BIC) in an experimental animal model.Material and MethodsTwelve 4-month-old New Zealand white rabbits were used. Following general anesthesia, 3-5 mL of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 20 publications
1
28
0
2
Order By: Relevance
“…Some studies have demonstrated that L‐PRF compressed clot alone produced favorable clinical outcomes in the treatment of infrabony periodontal defects (Chang et al, ; Zhao et al, ; Sharma and Pradeep, ; Ajwani et al, ; Chandradas et al, ), protected open wounds in the oral cavity (Asaka et al, ), sped up the healing of hard and soft tissues (Marenzi et al, ; Simon et al, ; Boora et al, ; Tunali et al, ; Eren et al, ; Kotsakis et al, ), reduced the rates of alveolitis after tooth extractions (Eshghpour et al, ; Kumar et al, ), and improved BV in preprosthetic surgeries and the osseointegration of dental implants (Oncu and Erbeyoglu, ; Castro et al, ; Cortese et al, ; Kanayama et al, ; Aoki et al, ; Oncu and Alaaddinoglu, ; Oncu et al, ; Boora et al, ; Simon et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that L‐PRF compressed clot alone produced favorable clinical outcomes in the treatment of infrabony periodontal defects (Chang et al, ; Zhao et al, ; Sharma and Pradeep, ; Ajwani et al, ; Chandradas et al, ), protected open wounds in the oral cavity (Asaka et al, ), sped up the healing of hard and soft tissues (Marenzi et al, ; Simon et al, ; Boora et al, ; Tunali et al, ; Eren et al, ; Kotsakis et al, ), reduced the rates of alveolitis after tooth extractions (Eshghpour et al, ; Kumar et al, ), and improved BV in preprosthetic surgeries and the osseointegration of dental implants (Oncu and Erbeyoglu, ; Castro et al, ; Cortese et al, ; Kanayama et al, ; Aoki et al, ; Oncu and Alaaddinoglu, ; Oncu et al, ; Boora et al, ; Simon et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the positive effect on soft and hard tissue healing, PRF can be used for its antihemorrhagic effects. These effects are important in reducing edema after surgery …”
Section: Introductionmentioning
confidence: 99%
“…These effects are important in reducing edema after surgery. [22][23][24] When the collagen membrane and PRF are compared, PRF has natural adhesive property. [22][23][24] It has high resistance due to the fibrin network in PRF and this feature can prevent graft particles from escaping into the sinus membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Membranes were also introduced to separate tissues. Recent research clearly indicates that L-PRF (leukocyte-platelet-rich fibrin, a second generation of platelet concentrates) significantly enhances wound healing in both soft and hard tissues [46].…”
Section: Introductionmentioning
confidence: 99%